Studying the Microstructure of Al-Ti Alloy Prepared by Powder Metallurgy using Three Different Percentages of Ti - Sahib Mohammed Mahdi; Nadia Ghadhanfer Hikmat; Dalmn Yaseen Taha (Journal of Engineering, 2020)
The effect of different Ti additions on the microstructure of Al-Ti alloy prepared by powder metallurgy was investigated. A certain amount of Ti (10wt%, 15wt%, and 20wt%) were added to aluminium and the tests like microhardness, density, scanning electron microscope (SEM), optical microscope (OM) and X-Ray Diffraction (XRD) were conducted to determine the influence of different Ti additives on the Al-Ti alloy properties and microstructure. The results show that the grains of α-Al changed from large grains to roughly spherical and then to small rounded grains with increasing Ti content, the micro-hardness of the alloy increases with increasing Ti, and XRD results confirm the formation of TiAl3 intermetallic compound during sintering.